The Effect of Career, Work Environment, and Organisation Culture on Employee Performance Dimediated by Job Satisfaction (Empirical Study: Employees of Loading and Unloading Transportation Companies in Jakarta) - Fachmy Erdiman; Christian Haposan Pangaribuan (Al-Makki Publisher, 2025)
This study aims to analyze the effect of career, work environment, and organizational culture on employee performance mediated by job satisfaction, especially in freight transport companies in Jakarta. In a competitive environment, understanding these factors is critical to improving employee performance. This study uses a quantitative approach with data collection through questionnaires. The sample consisted of 132 respondents who worked in freight transportation companies and had a minimum of five years of work experience. Data were analyzed using Smart-PLS 3.0 to test the relationship model between variables. The results of the analysis show that organizational culture has no significant effect on job satisfaction and employee performance. Career has a significant positive effect on job satisfaction, but has no direct effect on performance. The work environment is proven to have a positive and significant effect on job satisfaction and employee performance. In addition, job satisfaction has a significant positive effect on employee performance. This finding suggests that although the company has experienced an increase in profits, attention to career development and organizational culture still needs to be improved. A good work environment and high job satisfaction can drive better performance. This study concludes that to improve employee performance in freight transportation companies, it is important to focus on improving the work environment and job satisfaction. Although career has a positive effect on job satisfaction, greater attention needs to be paid to developing a supportive organizational culture.